PERAN PUSAT PELAYANAN ORANGTUA SEJAHTERA (PPOS) GBKP SIBOLANGIT TERHADAP KESEJAHTERAAN LANSIA DALAM PANTI - Emmy Silvia Br Tarigan; Husni Thamrin (STIE Wijaya Mulya, 2025)
This study explains the role of the Elderly Social Institution at the Sibolangit Prosperous Parent Service Center (PPOS) for the welfare of the elderly. This research focuses on the role played by the Prosperous Parent Service Center for the welfare of the elderly in it. This study uses a descriptive qualitative research method by collecting data by interview and direct observation of the object under study while also using literature study by collecting several documents that have a relationship with the object of research. Welfare is the right of every individual on earth, including the elderly. Even though the elderly are old and some body functions are not going well, the elderly are one of the individuals who deserve to get welfare and justice in social and social life. For this reason, with the existence of social institutions, it is hoped that it can develop the elderly according to their abilities, with the existence of a parent service center it is also hoped that it can restore the productivity of an elderly person and can restore the functioning of the elderly in their daily lives.Â Keywords : Role of Social Institutions, Social Institution Services, Prosperous Elderly, Elderly Welfare